2022
DOI: 10.5267/j.uscm.2022.3.005
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction, customer delight, customer retention and customer loyalty: Borderlines and insights

Abstract: The aim of this study is to investigate the effects of customer satisfaction and customer delight on customer loyalty through customer retention. Data were collected using a questionnaire developed based on the literature and administered to a sample of restaurant customers consisting of 376 customers. Using IBM SPSS and AMOS software for data analyses, the results indicate that customer retention had a perfect mediating role in the effect of customer satisfaction on customer loyalty and a partial mediating ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The sixth hypothesis was likewise addressed by the findings of the sixth study, which showed that customer loyalty is positively and significantly impacted by service quality (H6). As stated by Aityassine (2022) and Chao et al (2023), the quality of service felt by consumers is directly able to influence consumer loyalty. From the results and analysis obtained, it is known that there is an influence between the quality of legendary restaurant services on consumer loyalty.…”
Section: A Hypothesis Testingmentioning
confidence: 99%
“…The sixth hypothesis was likewise addressed by the findings of the sixth study, which showed that customer loyalty is positively and significantly impacted by service quality (H6). As stated by Aityassine (2022) and Chao et al (2023), the quality of service felt by consumers is directly able to influence consumer loyalty. From the results and analysis obtained, it is known that there is an influence between the quality of legendary restaurant services on consumer loyalty.…”
Section: A Hypothesis Testingmentioning
confidence: 99%
“…Customer retention has been studied due to four main factors: satisfaction, positive word of mouth, repeat purchase intent and loyalty to the company (Cheraghalizadeh & Dědková, 2022;Mohammed & Mahmood, 2022). Researchers have seen customer satisfaction as an important determinant of customer retention (Aityassine, 2022;Khwaja & Yang, 2022). Service companies will be more successful if they implement customer retention rather than customer satisfaction strategies (Sasono et al, 2021).…”
Section: Customer Retentionmentioning
confidence: 99%
“…Banking studies conducted in Botswana and Jordan, emphasise the importance of securing joyful experiences in a services context, to stimulate loyalty. In these studies, delight is positioned, in a banking context, as feelings of happiness since the bank can deliver over and above the expectations of customers, resulting in a desire to remain with the bank in the future (Svotwa et al, 2023;Aityassine, 2022). Accordingly, it is hypothesised that: H1.…”
Section: Theoretical Model Development Delight-loyalty Interrelationshipmentioning
confidence: 99%